2019
DOI: 10.1002/ijgo.12806
|View full text |Cite
|
Sign up to set email alerts
|

Serum estradiol level on trigger day impacts clinical pregnancy rate in modified natural frozen embryo transfer cycles

Abstract: Objective To examine the predictive value of serum estradiol and progesterone on the day of human chorionic gonadotropin (hCG) administration and embryo transfer for clinical pregnancy rate in modified natural‐cycle frozen embryo transfer (NC‐FET). Methods In a longitudinal prospective study, all eligible women who underwent NC‐FET cycles with hCG triggering in Royan Institute, Tehran, Iran, from June 1, 2015, to December 31, 2016, were evaluated. Serum estradiol and progesterone levels were measured at menstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Hull et al in a classical study showed that a lower threshold of 9.4 ng/ml was optimal for fertility in natural cycles [ 22 ]. Regarding FET cycles, Ramezanali et al [ 23 ] found that there was no significant difference in P 4 levels on the day of ET between pregnant and non-pregnant women (8.7 ± 0.5 versus 8.2 ± 0.5 ng/ml) in a longitudinal study of 101 modified natural FET cycles. In artificial cycles, current evidence suggests that P 4 levels of > 5 ng/ml provide an acceptably primed endometrium, resulting in endometrial luteinization and receptivity, which did not differ from that achieved by very higher levels [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hull et al in a classical study showed that a lower threshold of 9.4 ng/ml was optimal for fertility in natural cycles [ 22 ]. Regarding FET cycles, Ramezanali et al [ 23 ] found that there was no significant difference in P 4 levels on the day of ET between pregnant and non-pregnant women (8.7 ± 0.5 versus 8.2 ± 0.5 ng/ml) in a longitudinal study of 101 modified natural FET cycles. In artificial cycles, current evidence suggests that P 4 levels of > 5 ng/ml provide an acceptably primed endometrium, resulting in endometrial luteinization and receptivity, which did not differ from that achieved by very higher levels [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results founded that serum E 2 level on the day of HCG administration was an independent predictor of live‐birth achievement, and high serum E 2 level on HCG day was associated with decreased live‐birth rates in patients with FET. The impaired oocyte maturation and the decreased pregnancy achievement caused by elevated E 2 levels have been mentioned 34,35 . Clinical studies suggested that high E 2 levels could adversely affect perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired oocyte maturation and the decreased pregnancy achievement caused by elevated E 2 levels have been mentioned. 34,35 Clinical studies suggested that high E 2 levels could adversely affect perinatal outcomes. The occurrence of complications associated with abnormal placenta was significantly increased when serum E 2 level was at >10 000 pmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…However, Blazar et al [ 26 28 ] discovered that higher E 2 levels on hCG days predicted a greater number of oocytes, and any adverse impact on endometrial can be conquered in IVF-ET. Only the estradiol level on the hCG day was a significant predictive variable for clinical pregnancy [ 29 , 30 ]. Additionally, according to percentile curves, Papageorgiou et al [ 31 ] did not identify any deleterious effects of high E 2 levels.…”
Section: Introductionmentioning
confidence: 99%